2015
DOI: 10.3732/ajb.1400558
|View full text |Cite
|
Sign up to set email alerts
|

The Tetramerium lineage (Acanthaceae: Justicieae) does not support the Pleistocene Arc hypothesis for South American seasonally dry forests

Abstract: The South American genera Pachystachys, Schaueria, and Thyrsacanthus need to be recircumscribed. The congruence among biogeographical events found for the Tetramerium lineage suggests that the dry forest centers currently dispersed throughout South America are relatively old remnants, probably isolated since the Neogene, much earlier than the Last Glacial Maximum postulated by the Pleistocene Arc hypothesis. In addition to exploring the Pleistocene Arc hypothesis, this research also informs evolution in a line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 90 publications
4
29
0
1
Order By: Relevance
“…). This agrees with the idea of independent evolutionary histories among NSDF nuclei across their distribution (Becerra, ; Côrtes et al., ; de Melo et al., ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…). This agrees with the idea of independent evolutionary histories among NSDF nuclei across their distribution (Becerra, ; Côrtes et al., ; de Melo et al., ).…”
Section: Discussionsupporting
confidence: 91%
“…In fact, Pennington et al (2009) andLinares-Palomino et al (2011) suggested that widespread species in NSDFs are an exception: only 1.43% of plant species are recorded in~50% of the floristic nuclei defined across the region. This paucity of widespread NSDF species argues strongly against a widespread Pleistocene NSDF formation throughout the Neotropics, rather suggesting dispersal limitation in NSDF biota and a mixed evolutionary history across their distribution, with ecological similarities arising from climatic convergence (Cracraft, 1985;Mayle, 2004;Becerra, 2005;Côrtes et al, 2015;Banda et al, 2016;de Melo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Schaueria azaleiflora Rusby, which also possesses narrow bracts, together with species of Streblacanthus , form a grade basal to Pachystachys (our Fig. , based on results from Côrtes et al ). These relationships suggest that narrow bracts are plesiomorphic in the clade.…”
mentioning
confidence: 74%
“…For instance, although the type species of Streblacanthus, S. monospermus Kuntze, diverged near the root of the ‘ Tetramerium lineage’, the other three species of the genus form a grade near Pachystachys Nees (Daniel et al , our Fig. , based on results from Côrtes et al ).…”
mentioning
confidence: 78%
See 1 more Smart Citation